2017
DOI: 10.3390/ijms18102116
|View full text |Cite
|
Sign up to set email alerts
|

Prediction Potential of Serum miR-155 and miR-24 for Relapsing Early Breast Cancer

Abstract: Oncogenic microRNAs (oncomiRs) accumulate in serum due to their increased stability and thus serve as biomarkers in breast cancer (BC) pathogenesis. Four oncogenic microRNAs (miR-155, miR-19a, miR-181b, and miR-24) and one tumor suppressor microRNA (let-7a) were shown to differentiate between high-and low-risk early breast cancer (EBC) and reflect the surgical tumor removal and adjuvant therapy. Here we applied the longitudinal multivariate data analyses to stochastically model the serum levels of each of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 21 publications
1
27
0
Order By: Relevance
“…Based on previous microarray assay and RT-PCR data (11), miR-155, miR-96 and miR-99a were selected as candidate miRNAs for the diagnosis and prognosis of HCC. miR-155 acts as an oncogenic miRNA, which has been found to be upregulated in various types of tumor, such as breast cancer (15), gastric cancer (16), lung cancer (17), colorectal cancer (18) and other solid malignancies. Bašová et al (15) indicated that there was a positive correlation between miR-155 levels and the pathogenesis of early breast cancer relapse, particularly at the time of post-surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on previous microarray assay and RT-PCR data (11), miR-155, miR-96 and miR-99a were selected as candidate miRNAs for the diagnosis and prognosis of HCC. miR-155 acts as an oncogenic miRNA, which has been found to be upregulated in various types of tumor, such as breast cancer (15), gastric cancer (16), lung cancer (17), colorectal cancer (18) and other solid malignancies. Bašová et al (15) indicated that there was a positive correlation between miR-155 levels and the pathogenesis of early breast cancer relapse, particularly at the time of post-surgery.…”
Section: Discussionmentioning
confidence: 99%
“…miR-155 acts as an oncogenic miRNA, which has been found to be upregulated in various types of tumor, such as breast cancer (15), gastric cancer (16), lung cancer (17), colorectal cancer (18) and other solid malignancies. Bašová et al (15) indicated that there was a positive correlation between miR-155 levels and the pathogenesis of early breast cancer relapse, particularly at the time of post-surgery. These previous data suggested that oncogenic miRNAs (miR-155 and miR-24) in serum may enable not only the monitoring of early breast cancer, but may also become a highly valuable tool for the detection of relapse in patients with early breast cancer (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a matter of fact, microRNAs are crucial regulators of tumorigenesis and represent a new frontier in cancer diagnosis and prognosis, as well as in the prediction of therapeutic responsiveness. In this regard, recent evidence has proven the usefulness of miRNAs in disease progression monitoring [ 122 , 123 ]. Examples of miRNAs that were implicated in TEX-mediated functions include, but are not limited to, (i) miR-21, miR-141, miR-200a, miR-200c, miR-200b, miR-203, miR-205, and miR-214, all of which were found to be expressed in circulating TEXs isolated from ovarian cancer patients [ 124 ]; and (ii) miR-21 and miR-1246, identified as diagnostic and prognostic markers in exosomes from esophageal squamous cell cancer (ESCC) [ 125 , 126 , 127 ].…”
Section: Discussionmentioning
confidence: 99%
“…And multivariate analysis revealed that miR-24-3p could be an independent prognostic indicator for OS of CRC patients ( 10 ). In breast cancer, miR-24 was identified to be highly predictive of early breast cancer relapse ( 38 ). In nasopharyngeal carcinoma, a survey proved that exosomal miR-24-3p could serve as a prognostic biomarker, due to its involvement in tumor pathogenesis by mediating T-cell inhibition ( 25 ).…”
Section: Therapeutic Relevance Of Mir-24 In Cancermentioning
confidence: 99%